JELLY CANDY FORMULATION WITH THE ADDITION OF MANGROVE APPLE LEAF EXTRACT (Sonneratia caseolaris L) - Prima, Adeta; Gusriani, Ika; Muhaimin, Muhaimin (Universitas Wahid Hasyim, 2023)
This study aims to determine the effect of adding Mangrove Apple Leaf extract to jelly candy and to determine the best formulation for jelly candy from Mangrove Apple Leaf extract. The experimental design used was a randomized block design with five treatment levels, namely the addition of extract concentrations of 300 ml (42%), 400 ml (49%), 500 ml (54%), 600 ml (58%), and 700 ml (62%). Parameters tested included pH, total dissolved solids, water content, texture, color degree, antioxidant analysis, and organoleptic (taste, texture, and overall acceptability). The results of the jelly candy test from Mangrove Apple Leaf extract significantly affected the values of water content, texture, antioxidant activity, organoleptic taste, texture, and overall acceptability. However, they did not significantly affect total dissolved solids, degree of acidity (pH), or color. The best concentration in this study was the addition of 58% pedada leaf extract, which had a pH value of 5.4; total dissolved solids 13.42 0Brix; water content 56.44%; texture test 727.5 gf; antioxidant activity 72.74%; yellow red color description, slightly sweet taste, peppermint aroma and overall acceptability close to like